Effects of urolithin A on osteoclast differentiation induced by receptor activator of nuclear factor-κB ligand via bone morphogenic protein 2. Issue 3 (1st March 2022) - Wang, Zhe; Qi, Guobin; Li, Zhuokai; Cui, Xu; Guo, Shengyang; Zhang, Yueqi; Cai, Pan; Wang, Xiuhui
ABSTRACT: Urolithin A (UA) is an intestinal microbial metabolite derived from ellagitannins and a promising agent for treating osteoarthritis. However, its effects on osteoporosis are unclear. This study explored the effects of urolithin A (UA) on receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclasts and its underlying molecular mechanisms. RANKL treatment significantly increased tartrate-resistant acid phosphatase (TRACP) or osteoclast marker levels ( P < 0.05), while adding UA decreased the RANKL-induced levels ( P < 0.05) in RAW264.7 cells. Total RNA isolated from RANKL- or RANKL + UA-treated cells was sequenced, and the obtained transcriptome dataset revealed 2, 399 differentially expressed genes. They were enriched in multiple pathways involved in rheumatoid arthritis, ERK1 and ERK2 cascade, regulation of inflammatory response, ECM-receptor interactions, and TNF signaling. Scanning electron microscopy showed that RANKL promoted bone resorption pits in bone biopsy specimens, whereas UA inhibited their formation. When bone morphogenic protein 2 (BMP2) was shRNA -silenced, the bone resorption pits were restored. Moreover, while RANKL significantly enhanced the levels of p-ERK2/ERK2, p-p38/p38, p-Akt1/Akt1, p-ERK1/ERK1, and osteoclast-related proteins ( P < 0.05), UA reduced them. BMP2 silencing also reversed the UA inhibitory effect. Thus, UA represses the RANKL-induced osteoclast differentiation of RAW264.7 cells by regulating Akt1, p38, and ERK1/2 signaling, and BMP2 likely reverses the UA inhibitory effect via these pathways. We propose BMP2 as a potential drug target for treating bone metabolic diseases, such as osteoporosis. GRAPHICAL ABSTRACT: uf0001